2021
DOI: 10.1186/s12893-021-01172-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain and postoperative nausea and vomiting and their association in the early postoperative period: an observational study from Palestine

Abstract: Background Postoperative nausea and vomiting (PONV) and postoperative pain (POP) are most commonly experienced in the early hours after surgery. Many studies have reported high rates of PONV and POP, and have identified factors that could predict the development of these complications. This study aimed to evaluate the relationship between PONV and POP, and to identify some factors associated with these symptoms. Methods This was a prospective, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
2
7
0
1
Order By: Relevance
“…As is known, pain has a stimulating effect on GIS (28,33). The results of our study bear similarities to the results of other studies found in the literature (34,35). We can correlate higher distress levels regarding nausea/vomiting/retching in patients with surgical history with the fact that they have experienced PONV before.…”
Section: Discussionsupporting
confidence: 89%
“…As is known, pain has a stimulating effect on GIS (28,33). The results of our study bear similarities to the results of other studies found in the literature (34,35). We can correlate higher distress levels regarding nausea/vomiting/retching in patients with surgical history with the fact that they have experienced PONV before.…”
Section: Discussionsupporting
confidence: 89%
“…The SAPB reduces the incidence of PONV which is a common postoperative complication following general anesthesia (32). The PONV can reduce patient comfort, affect postoperative rehabilitation, and can lead to serious complications, such as aspiration pneumonia, asphyxia, water-electrolyte disorders and dehydration in severe patients, reduced surgical and anaesthetic safety, increased burden on medical and nursing staff, as well as patients' economic burden (33). It can also lead to or aggravate postoperative anxiety, enhance psychological stress, affect hemodynamic stability, and reduce patient' pain threshold (34).…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative stress response to surgery for many old people is more severe than that of young people. The symptoms are nausea and vomiting after general anesthesia [ 22 24 ]. This leads to decreased digestive and absorption functions of the gastrointestinal tract, resulting in loss of appetite and eating less.…”
Section: Discussionmentioning
confidence: 99%